Analysis Of the Role of Strategic Management Accounting in The Implementation of Sustainable Development Goals on PT NSI - Langgeng Harum Islami; Yanuar Ramadhan; Jatis Mara Jatmika; Gatot Apriantoro (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2022)
This research discusses the importance of implementing the Sustainable Development Goals relating to eradicating poverty, which is the 1st SDGs goal, and decent work and economic growth, which are the 8th of the 17 SDGs goals. The purpose of this research is to provide advice to companies to contribute to eradicating poverty and decent work and economic growth by creating jobs that will benefit companies, society, and the government in general. This study uses a descriptive analysis approach by means of a literature review at PT NSI engaged in retail. The results of the study show that PT NSI has not maximized the implementation of the Sustainable Development Goals related to goals 1 and 8. The lack of training to improve human resources and the large number of employees who are still below the poverty line at PT NSI are one of the problems. The limitation of this research is the lack of financial data so that it cannot be proven statistically. The implication of this research is that PT NSI s contribution to achieving the SDGs goals will make the company recognized by the state and accepted by the community.